2009
DOI: 10.1186/ar2844
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin may contribute to synovitis and joint destruction in rheumatoid arthritis by stimulating vascular endothelial growth factor, matrix metalloproteinase-1, and matrix metalloproteinase-13 expression in fibroblast-like synoviocytes more than proinflammatory mediators

Abstract: IntroductionThe role of adiponectin in the pathogenesis of arthritis is still controversial. This study was performed to examine whether adiponectin is involved in joint inflammation and destruction in rheumatoid arthritis (RA) in relation to the expression of vascular endothelial growth factor (VEGF) and matrix metalloproteinases (MMPs).MethodsSynovial cells from RA patients were treated with adiponectin or interleukin (IL)-1β for 24 hours. The culture supernatant was collected and analyzed for the levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
80
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 31 publications
2
80
1
Order By: Relevance
“…It can regulate the enzymatic activity of other MMPs such as MMP-1 and MMP-9, and promote collagen degradation, extracellular matrix destruction, and joint swelling, to reduce resistance to external force. With the help of the stress load, it can cause cartilage destruction (Choi et al, 2009;Tong et al, 2011). Our study showed that MMP-3 levels were significantly elevated in articular cartilage lesions.…”
Section: Discussionmentioning
confidence: 59%
“…It can regulate the enzymatic activity of other MMPs such as MMP-1 and MMP-9, and promote collagen degradation, extracellular matrix destruction, and joint swelling, to reduce resistance to external force. With the help of the stress load, it can cause cartilage destruction (Choi et al, 2009;Tong et al, 2011). Our study showed that MMP-3 levels were significantly elevated in articular cartilage lesions.…”
Section: Discussionmentioning
confidence: 59%
“…Of note, adiponectin serum levels in patients with RA but not in patients with OA correlate with VEGF levels (33). Interestingly, other key factors driving arthritis such as TNF␣ and IL-1␤ were not induced by adiponectin in RASFs (26).…”
Section: Adiponectin In Ramentioning
confidence: 95%
“…When stimulated with adiponectin, synovial fibroblasts (SFs), the central cells of cartilage destruction in RA, secrete increased amounts of proinflammatory cytokines such as IL-6, a variety of chemokines including IL-8 and growth-related oncogene ␣, proangiogenic factors such as vascular endothelial growth factor (VEGF), and matrix-degrading proteins including matrix metalloproteinase 1 (MMP-1) and MMP-13 (26,(33)(34)(35)(36). Of note, adiponectin serum levels in patients with RA but not in patients with OA correlate with VEGF levels (33).…”
Section: Adiponectin In Ramentioning
confidence: 99%
“…It was demonstrated that adiponectin increased infl ammatory interleukin-6 (IL-6) (26) and interleukin-8 (27) in synovial fi broblast cells. Besides, the upregulation of matrix metalloproteinase (MMP) -1 and -13 genes expression level in fi broblast-like cell was demonstrated by Choi et al (28). The relationship between adiponectin and other MMPs (MMP-2 and MMP-3) was also showed by other researchers (29,30).…”
Section: Discussionmentioning
confidence: 87%